Comment évaluer et mesurer la conflictualité liée aux usages de l’espace ? Eléments de méthode et de repérage - André Torre; Romain Melot; Luc Bossuet; Anne Cadoret; Armelle Caron; Ségolène Darly; Philippe Jeanneaux; Thierry Kirat; Haï Vu Pham (VertigO)
This article aims to present the research conducted in recent years by a multidisciplinary team on the questions of land-use conflict, and to reveal the methodology of survey and data collection, as well as the structure of the resulting database. We first define the scope of our study by providing a definition of these conflicts, of their characteristics and motives, of the ways they manifest themselves and of the actors involved. We then present the methodology we have used to identify conflicts ; a methodology based on a spatial analysis and the combined use of different data collection methods including surveys conducted by experts,  analyses of the regional daily press and of data from the administrative litigation courts. Finally we present the Conflicts data base©, with its tables and nomenclatures, in which the data collected in different fields is reconciled and analysed (III), before providing a few examples of how this method can be used to analyse the case of the Greater Paris Region.